The Aesthetics of Learning: Factors Shaping Art Spaces in High School Libraries - Cuong, Pham Hung (Journal of Ecohumanism, 2024)
This study explores the diverse factors influencing the aesthetics of learning within high school libraries in Hanoi, Vietnam, highlighting the transition of these spaces from traditional book repositories to dynamic learning environments. Employing a structured questionnaire administered to 200 teachers and school administrators, the research utilizes multiple linear regression analysis to investigate the impact of physical layout, institutional policy, educational objectives, student engagement, technological integration, and cultural and community influences on learning aesthetics. The results reveal significant positive contributions from the physical layout, institutional policy, educational objectives, student engagement, and technological integration. In contrast, cultural and community influences did not show a significant effect, indicating a more complex relationship between local culture and educational aesthetics that may require deeper analysis. These findings provide valuable insights for educational policymakers and school administrators by underscoring the importance of strategic design and resource allocation in enhancing library environments to bolster learning outcomes. The study addresses a critical gap in the existing academic literature and offers actionable recommendations for optimizing library spaces’ aesthetic and functional aspects to enhance educational effectiveness.